Mobile guide technologies (smartphone apps): Collaborative Heuristic Evaluation (CHE) with expert and novice users - Mohd Kamal, Othman; Fadhullah, Mahudin; Cassandra Henry, Ahaguk; Muhd Farhan, Abdul Rahman (2015)
Providing quality and meaningful experiences to the users are vital particularly with the devices that users are familiar with. Usability issues should be discarded before the systems/designs are deployed to the users. In this study, we compared the usability issues found by expert and novice users using Collaborative Heuristic Evaluation (CHE). This study was carried out with 6 experts and 9 novice users. There are 3 different mobile guides used in this study, 2 were designed to be used in museum and another mobile guide was designed to be used at a tourist attraction. Results showed that expert users found significantly more heuristic problems than novice users during the CHE procedure across the 3 different mobile guides (smartphone apps). On the other hand, there were heuristic problems found by the novices that were not noticeable to the expert.